2005
DOI: 10.1111/j.1349-7006.2005.00031.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of novel LERGU mRNAs in GPR30 3′ untranslated region and detection of 2 bp‐deletion polymorphism in gastric cancer

Abstract: The improved IGCR (In-Gel Competitive Reassociation) method was applied to the analysis of human gastric cancer genomic DNA to identify its alterations, and it appeared that the IGCR library contained a fragment of 3′ ′ ′ ′-untranslated region (3′ ′ ′ ′ UTR) of G-protein coupled receptor 30 (GPR30) mRNA. When we searched genomic DNA pairs of gastric cancer patients with this IGCR clone, we found the deletion polymorphism with or without 2 bp (Cytosine and Thymine; CT). We confirmed the existence of a novel mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Among the 40 SNPs identified in the GPER gene (GenBank accession no. NM_001039966), only four were reported to be associated with human neoplasms, according to the internet database [37] The first of these four SNPs has been reported in gastric cancer [38] and creates an alternative splice site that produces a frameshift protein with no cellular relevance. The other three SNPs are associated with aggressive histopathological characteristics of breast cancers [39].…”
Section: Resultsmentioning
confidence: 99%
“…Among the 40 SNPs identified in the GPER gene (GenBank accession no. NM_001039966), only four were reported to be associated with human neoplasms, according to the internet database [37] The first of these four SNPs has been reported in gastric cancer [38] and creates an alternative splice site that produces a frameshift protein with no cellular relevance. The other three SNPs are associated with aggressive histopathological characteristics of breast cancers [39].…”
Section: Resultsmentioning
confidence: 99%
“…Applying "reverse translational medicine" we should rethink our therapeutic approaches when using these drugs which also suggest possible new therapeutic indications such as for the treatment of bleeding in hereditary heamorrhagic telangiectasia [182] and possibilities for future drug development. Medical genetics studies have found that genetic polymorphisms of GPER are associated with changes in cell function [183] or disease susceptibility for dyslipidemia [73], arterial hypertension [108], seminoma [184], gastric cancer [185], breast cancer [186], leiomyoma [187] and gynecomastia in adolescents [188] providing us with new opportunities for personalized medicine, theranostics, and thereby improving treatment and prevention. Continued clinical research is required to increase our understanding of estrogen receptors and the clinically approved drugs targeting them and how these drugs mediate therapeutic benefits and unwanted side effects in patients, which ultimately will improve patient safety and survival.…”
Section: Discussionmentioning
confidence: 99%
“…56,57 For example, the deletion of 2 bp (cytosine and thymine; CT) in the 3'-UTR of the G-protein coupled receptor 30 (GPR30) mRNA may produce a frame-shifted protein that leads to gastric cancer. 58 In the population-based case-control study Cancer Prostate in Sweden (CAPS), a sequence variant (11381G/C) in the 3'-UTR of TLR4 was found to be associated with elevated prostate cancer risk. 9 However, in our study on the pathogenetics of NPC, the variation in the 3'-UTR of TLR4 was 11350G/C.…”
Section: Discussionmentioning
confidence: 99%